If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -90 = -10(-3b) Remove parenthesis around (-3b) -90 = -10 * -3b Multiply -10 * -3 -90 = 30b Solving -90 = 30b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-30b' to each side of the equation. -90 + -30b = 30b + -30b Combine like terms: 30b + -30b = 0 -90 + -30b = 0 Add '90' to each side of the equation. -90 + 90 + -30b = 0 + 90 Combine like terms: -90 + 90 = 0 0 + -30b = 0 + 90 -30b = 0 + 90 Combine like terms: 0 + 90 = 90 -30b = 90 Divide each side by '-30'. b = -3 Simplifying b = -3
| x^3=5x-4x^2 | | (3x^2-4x+2)+(x^2+3x-4)= | | 4e+9= | | -(2-4(-3+1)+2)/9(-1-2) | | 0=8x-x^3 | | 102-6x=21x+18 | | (2x^2+3x-1)+(4-6x)= | | 50=-5(5p) | | (1450-105/1450)100=x | | (1450-105/1450)100=0 | | 2=31/4+n | | x^3-17x^2+90x-144=0 | | 0=(16x^2)+400 | | (1450-y/1450)100=.928 | | 5x+30=x+2 | | x-7=4x+2 | | x+46=5x+22 | | (a+(3a))/b/(9+a)/b | | 4x-21=x+6 | | -0.6-0.4y=1.4 | | 5x-16=2x+5 | | 5x-13=x+3 | | -2x-11=x+1 | | 5x+11=x+3 | | x-3=5x+21 | | 1282-2x= | | 2.22-0.57s=-1.85/0.74 | | 2.22-0.57s=-1.85/08.74 | | 5x+8+6=8x+9-9 | | 45+1x= | | -3x+1=x+9 | | -2+n^2+n=0 |